Penguatan Spiritualitas Santriwati melalui Seminar Psikologi Qur’ani: Refleksi Makna Hidup dan Kebahagiaan di Pondok Pesantren Sunan Drajat - Hasanah, Muhimmatul; Zunaih, Ahmad Iwan; Kustina, Farikha (Keris: Journal of Community Engagement, 2025)
This community engagement program aims to enhance the understanding of life’s meaning and authentic happiness among female students (santriwati) at Pondok Pesantren Sunan Drajat through the integration of Qur’anic values and existential psychology. The program was motivated by the increasing phenomenon of existential crisis and identity confusion among adolescents in pesantren settings, which often lacks systematic psycho-spiritual intervention. The activity was implemented in the form of a one-day reflective-educational seminar, consisting of three sessions: exploring the concept of life’s meaning in the Qur’an, integrating Viktor Frankl’s logotherapy, and conducting guided personal reflection. Evaluation methods included pre- and post-tests as well as thematic analysis of written reflections. Results showed a 15% increase in comprehension scores and a significant cognitive shift in participants’ perspectives toward life’s hardships, from obstacles to opportunities for spiritual growth. Participant reflections indicated that Qur’anic values such as sabr (patience), shukr (gratitude), and tawakkul (trust in God) served as sources of psychological resilience and inner peace. The findings suggest that a Qur’anic psychology approach is both relevant and effective in strengthening character and emotional well-being in pesantren adolescents. Follow-up initiatives include mentoring and the development of a structured Qur’anic reflection module.